Modifying EFL communicative language teaching for Indonesian context - Sugeng Susilo Adi (UPT P2M Politeknik Negeri Malang, 2012)
This article is talking about the problems of implementing Communicative language teaching (CLT) in Indonesia. The main problem of applying the teaching approach is the gap between the theory and its classroom practices. Other problems such as classroom size in term of student number and student learning styles are also highlighted in this article. Accordingly, this article suggests an audio-lingual communicative language teaching strategies that might be applicable for the majority of Indonesian junior and senior high schools. These strategies were derived from empirical research that the writer conducted in Islamic Junior High Schools in Indonesia.